2011
DOI: 10.1139/f2011-072
|View full text |Cite
|
Sign up to set email alerts
|

A deathly odor suggests a new sustainable tool for controlling a costly invasive species

Abstract: Here we confirm a long-standing anecdotal observation; the sea lamprey ( Petromyzon marinus ) actively avoids the odor emitted by decaying conspecifics. We extracted the semiochemical mixture produced by the putrefying carcasses of sea lampreys via Soxhlet extraction in ethanol and exposed groups of 10 migratory-phase lampreys to either the putrefaction extract (N = 8) or an ethanol control (N = 8) in a laboratory raceway. Sea lampreys rapidly avoided the putrefaction odor while exhibiting no response to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 12 publications
4
64
0
Order By: Relevance
“…Several studies have recently supported that damage‐released alarm cues may serve as a promising addition to the integrated control methods of this formidable invasive species (Wagner et al , ; Bals & Wagner, ; Imre et al , ). Further, Imre et al () investigated whether migratory‐stage P .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently supported that damage‐released alarm cues may serve as a promising addition to the integrated control methods of this formidable invasive species (Wagner et al , ; Bals & Wagner, ; Imre et al , ). Further, Imre et al () investigated whether migratory‐stage P .…”
Section: Introductionmentioning
confidence: 99%
“…marinus recognize and respond to chemosensory alarm cues. Wagner et al () demonstrated in a semi‐natural experimental study that the proportion of adult P . marinus on the side of a laboratory stream channel scented with decaying P .…”
Section: Introductionmentioning
confidence: 99%
“…Twohey et al, 2003 Chemosensory alarm cues Natural repellents to force individuals into management areas Direct adults from low quality habitats/ streams and direct to areas of favorable habitat. Imre et al, 2010;Wagner et al, 2011 application, especially in large rivers (McLean, 2014). The trapping can also be highly selective for P. marinus 650 (McLaughlin et al, 2007).…”
Section: Trappingmentioning
confidence: 99%
“…such as the conspecific deathly odor (Wagner et al, 2011), conspecific injury-released alarm cues , heterospecific damage-released stimuli , and predator chemosensory cues . In their invasive 815 range, these could be used as repellents to manipulate migratory behaviors and thus have potential application to population control (Imre et al, 2010) to increase with climate change due to predicted hydrological alterations that result from more unpredictable precipitation patterns (Morrongiello et al, 2011).…”
mentioning
confidence: 99%